Hubungan Status Gizi dengan Usia Menarche : Relationship between Nutritional Status and Age of Menarche - Enggar Enggar; Ni Putu Suastuti; Ni Made Rosiyana (Jurnal Bidan Cerdas, 2022)
Introduction: Early menarche age is associated with an increase in body mass index. Nutrient intake also affects the sexual maturity of adolescent girls. Adolescent girls who get early menarche tend to have more weight and height than those who have not. The purpose of this study was to determine the relationship between nutritional status and age of menarche at SMP Negeri 6 Palu. Methods:  This study uses a cross sectional approach, a sample of 45 people from March to July 2020 using purposive sampling technique, measuring nutritional status using BMI and data analysis using chi square. The results showed that there was no relationship between nutritional status and age at menarche, p-value 0.542. The age at which menarche occurs is not affected by either being thin, normal or obese. It is advisable for young women to eat a balanced diet to maintain a healthy nutritional status during menarche. Inadequate nutrition will interfere not only with growth and organ function, but also reproductive function, especially menstrual disorders.     ABSTRAK Pendahuluan: Cepatnya usia Menarche dikaitkan dengan meningkatnya Indeks Masa Tubuh. Asupan zat gizi juga mempengaruhi kematangan seksual remaja putri. Remaja putri yang mendapatkan Menarche dini cenderung memiliki berat badan dan tinggi badan yang lebih dibandingkan dengan yang belum Menarche. Tujuan penelitian ini untuk mengetahui hubungan status gizi dengan usia Menarche di SMP Negeri 6 Palu. Metode: Penelitian ini menggunakan pendekatan cross sectional, sampel 45 orang pada bulan Maret sampai Juli 2020 menggunakan teknik purposive sampling, pengukuran status gizi menggunakan IMT dan analisis data menggunakan chi square. Hasil penelitian didaptkan bahwa tidak ada hubungan antara status gizi dengan usia menarche p-value 0,542. usia menarche terjadi tidak dipengaruhi  baik dari kurus, normal atau gemuknya seseorang. Sebaiknya remaja putri mengonsumsi makanan dengan gizi seimbang untuk menjaga status gizi yang sehat selama menarche. Gizi yang tidak adekuat akan mengganggu tidak hanya pertumbuhan dan fungsi organ tubuh, tetapi juga fungsi reproduksi terutama gangguan mentrusi.